A de novo SIX1 variant in a patient with a rare nonsyndromic cochleovestibular nerve abnormality, cochlear hypoplasia, and bilateral sensorineural hearing loss. Issue 12 (8th October 2019) - Kari, Elina; Llaci, Lorida; Go, John L.; Naymik, Marcus; Knowles, James A.; Leal, Suzanne M.; Rangasamy, Sampath; Huentelman, Matthew J.; Friedman, Rick A.; Schrauwen, Isabelle
Abstract: Background: Childhood hearing impairment affects language and cognitive development. Profound congenital sensorineural hearing impairment can be due to an abnormal cochleovestibular nerve (CVN) and cochleovestibular malformations, however, the etiology of these conditions remains unclear. Methods: We used a trio‐based exome sequencing approach to unravel the underlying molecular etiology of a child with a rare nonsyndromic CVN abnormality and cochlear hypoplasia. Clinical and imaging data were also reviewed. Results: We identified a de novo missense variant [p(Asn174Tyr)] in the DNA‐binding Homeodomain of SIX1, a gene which previously has been associated with autosomal dominant hearing loss (ADHL) and branchio‐oto‐renal or Branchio‐otic syndrome, a condition not seen in this patient. Conclusions: SIX1 has an important function in otic vesicle patterning during embryogenesis, and mice show several abnormalities to their inner ear including loss of inner ear innervation. Previous reports on patients with SIX1 variants lack imaging data and nonsyndromic AD cases were reported to have no inner ear malformations. In conclusion, we show that a de novo variant in SIX1 in a patient with sensorineural hearing loss leads to cochleovestibular malformations and abnormalities of the CVN, without any other abnormalities. Without proper interventions, severe to profound hearing loss is devastating to both education and social integration. Choosing the correct intervention can be challenging and a molecular diagnosis may adjust intervention and improve outcomes, especially for rare cases. Abstract : Our work describes a novel variant of SIX1 identified to likely be associated with congenital abnormality of the cochleovestibular nerve and congenital pediatric hearing loss.